Rewiring faces: advances and outcomes in facial nerve reconstruction after facial vascularized composite allotransplantation - Knoedler, Leonard; Niederegger, Tobias; Munzinger, Robert; Joshi, Surbhi; Schaschinger, Thomas; Cetrulo, Curtis L.; Festbaum, Christian; Kehrer, Andreas; Hundeshagen, Gabriel; Heiland, Max; Koerdt, Steffen; Neckel, Norbert; et al. (Frontiers in Surgery, 2026)
BackgroundFacial vascularized composite allotransplantation (FVCA) provides transformative restoration for patients with severe craniofacial defects, but successful outcomes depend heavily on facial nerve (FN) reconstruction and reinnervation. Unlike standard nerve repair, FN coaptation in FVCA must address donor–recipient mismatch and immunologic variability. This systematic review synthesizes clinical and preclinical evidence on FN reconstruction strategies in FVCA and their functional outcomes.MethodsThis review adhered to PRISMA 2020 guidelines and was registered with PROSPERO (ID: CRD420251029430). A comprehensive search of PubMed, EMBASE, Cochrane Library, Web of Science, and Google Scholar. Methodological quality was assessed using the Newcastle-Ottawa Scale (NOS) and SYRCLE tool for preclinical studies.ResultsOverall, n = 45 (11%) studies [n = 41 (91%) human, n = 4 (9%) preclinical] published between 2006 and 2025 were included. Human studies were predominantly case reports n = 18 (44%), case series n = 11 (27%), and cadaveric investigations n = 9 (22%). Across n = 139 (100%) documented nerve repair interventions (NRIs), direct coaptation was performed in n = 20 (14%), most commonly at the FN trunk or its buccal, zygomatic, marginal mandibular, and frontal branches n = 28 (20%). Nerve grafting was more frequent, in n = 62 (45%), typically using great auricular or thoracodorsal donor nerves; only n = 2 (1.4%) NRIs employed dual-level trunk and branch coaptation. Synkinesis was reported in n = 11 (7.9%) NRIs, and patient-reported outcomes, though inconsistently collected, indicated improvements in oral continence, speech, social integration, and psychosocial well-being. Secondary revisions occurred in n = 27 (19%) and infectious complications in n = 12 (8.6%) NRIs. Preclinical rodent and porcine models corroborated clinical evidence that combined motor and sensory nerve repair enhances functional recovery.ConclusionFN reconstruction in FVCA is feasible and often results in partial functional recovery. However, outcomes remain heterogeneous and are influenced by surgical approach, immunologic status, and rehabilitative support. Standardized assessment tools should be more widely adopted to improve comparability and guide individualized treatment planning. Translational research and multicenter data collection are needed. FN reconstruction represents both a clinical challenge and an opportunity to improve long-term quality of life in FVCA recipients. Systematic Review Registration: identifier CRD420251029430.